Pendampingan Ruang Terbuka Publik di Aceh - Sitompul, Rabita Akbari (PT. Arsil Reka Engineering, 2026)
Assistance in designing public open space plays a crucial role in creating a healthy and inclusive urban environment. In Aceh, the need for public open spaces is increasingly pressing due to standard minimum quantity 30% of open space in the city. Moreover,the demand of open space is increase because population growth, urbanization, and changes in people's lifestyles. Open spaces such as city parks serve social functions (recreation, sports, and interaction between residents) and cultural (as a platform for expressing the local identity), ecological functions (improving environmental quality and reducing microclimate temperatures), aesthetic functions (environmental beauty), and economic functions. However, many public spaces have not been able to fulfill their functions optimally. The stages of the activities carried out include site measurements, design concepts and pra-design. The tools used are AutoCAD, Sketchup, and Adobe Photoshop. This activity produces a final product in the form of a pradesign and a three-dimensional (3D) perspective. The design applies the design principles of balance, rhythm, accentuation, unity, proportion and simplicity. The resulting open space design applies active zoning to accommodate social and economic activities, and uses softscape and hardscape elements that can shape the microclimate.